Navigating the grey area: International college students’ knowledge and perceptions of Title IX - Smith, Lindsay; Swartz, Pallie; Irvin-Erickson, Yasemin (Journal of International Students, 2024)
International college students (ICS) in the United States (US) face challenges reporting and accessing services in cases of sexual harassment because they are not aware of the US laws that prohibit sexual violence. This lack of awareness along with cultural barriers may influence the odds of help-seeking among ICS in the US who experience sexual harassment. Minimal research to date has captured ICS’ knowledge and perceptions of Title IX regulations in the US which protects people from discrimination based on sex and gender in educational programs. Our study examined ICS’ knowledge and perceptions of Title IX through in-depth discussions with 13 ICS at a US university. Overall, ICS were not well-informed about Title IX and encouraged colleges to unpack the legal nature of Title IX for ICS who may not have encountered something similar to Title IX as it is “uniquely American.” Practical implications for improving campus resources are discussed.